Limiting efficiencies for intermediate band solar cells with partial absorptivity: the case for a quantum ratchet. (10th February 2016) - Pusch, Andreas; Yoshida, Megumi; Hylton, Nicholas P.; Mellor, Alexander; Phillips, Chris C.; Hess, Ortwin; Ekins‐Daukes, Nicholas J.
Abstract: The intermediate band solar cell (IBSC) concept aims to improve upon the Shockley–Queisser limit for single bandgap solar cells by also making use of below bandgap photons through sequential absorption processes via an intermediate band (IB). Current proposals for IBSCs suffer from low absorptivity values for transitions into and out of the IB. We therefore devise and evaluate a general, implementation‐independent thermodynamic model for an absorptivity‐constrained limiting efficiency of an IBSC to study the impact of absorptivity limitations on IBSCs. We find that, due to radiative recombination via the IB, conventional IBSCs cannot surpass the Shockley–Queisser limit at an illumination of one Sun unless the absorptivity from the valence band to the IB and the IB to the conduction band exceeds ≈36 % . In contrast, the introduction of a quantum ratchet into the IBSC to suppress radiative recombination can enhance the efficiency of an IBSC beyond the Shockley–Queisser limit for any value of the IB absorptivity. Thus, the quantum ratchet could be the vital next step to engineer IBSCs that are more efficient than conventional single‐gap solar cells. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : We devise and evaluate a general thermodynamic model for an absorptivity‐constrained limiting efficiency to study the impact of absorptivity limitations intermediate band solar cells (IBSCs). Conventional IBSCs cannot surpass the ShockleyŰQueisser limit at an illumination of one Sun unless the absorptivity from the valence band to the intermediate band (IB) and the IB to the conduction band exceeds 36%. Introducing a quantum ratchet into the IBSC to suppress radiative recombination can enhance the efficiency beyond the ShockleyŰQueisser limit for any value of the IB absorptivity.